Summability of series in the root functions of boundary-value problems of Bitsadze-Samarskii type - Aliev, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate the Abel summability of a system of eigenfunctions and associated functions of Bitsadze-Samarskii-type boundary-value problems for elliptic equations in a rectangle. These problems are reduced to a boundary-value problem for elliptic operator differential equations with an operator in boundary conditions in the corresponding spaces and are studied by the method of operator differential equations.